Antimicrobial activity of plant extracts of spices from northern Brazil (Research, Society and Development, 2022)
The use of plants for medicinal purposes is an ancient practice, in recent decades their use has grown due to the chemical composition of plant species. In Brazil it is possible to find a great diversity of species, most of which are found in the Amazon rainforest, one of the largest sources of raw material, with medicinal plants with phytotherapic properties. The objective of this work was to evaluate plant extracts of spices from the northern region against Staphylococcus aureus (ATCC 33591) and Escherichia coli (ATCC 25922) bacteria, evaluating their antimicrobial activity, identifying their chemical composition and yield of extracts obtained from the vegetable. The samples used were chicory (Eryngium foetidum L.), coriander (Coriandrum sativum L.) and jambú (Acmella oleracea (L.) RK Jansen), acquired in the municipal market of Santarém, in the state of Pará. The extracts were obtained through of the solid-liquid extraction method, carrying out the phytochemical identification through tests with specific reagents. In antimicrobial research, disk diffusion was used. The yield of extracts varied according to the reagent used. The chicory extract showed yields of 0.76%, 46.29%, 55.02% and 9.5%, coriander 60.5%, 48.97%, 3.73% and 18.54% and jambu 2.56%, 16.66%, 5.08% and 6.92% for hexane solvents. chloroform, ethyl acetate and ethanol, respectively. The antimicrobial assay against S. aureus strains obtained inhibition halos of 10 to 11 mm for chicory, 7 to 10 mm for coriander and 8 to 14 mm for jambú. The E.coli bacterium was not sensitive to the tested extracts. It is concluded that the tested plant extracts were effective against Staphylococcus aureus, making it a therapeutic alternative for infections caused by this bacterium.